Desarrollo De Un Nanocompuesto Fe3o4@Sio2 Como Potencial Nanotrasportador De Fármacos Para El Tratamiento Contra El Glioblastoma Multiforme (2023)
Among all the treatments for glioblastoma multiforme, chemotherapy is the most widespread because of anticancer drugs, which help shrink the tumor. Unfortunately, these drugs present several problems, such as the resistance of cancer cells and their low specificity. Using nanocarriers of these drugs is a novel strategy that can reduce the side effects associated with chemotherapy and thus obtain treatment with a lower burden on the body.